"America Will Educate Me Now": What Do Iraqi Refugees with Special Immigrant Visas Deserve and Who Decides? - Jill Koyama (Journal on Education in Emergencies)
Although thousands of Iraqi refugees who worked with the Allied Forces during the Iraq war have been resettled in the United States, little is known about their experiences. In the aggregate, they are a well-educated, multilingual subset of refugees who aspire to earn college and higher education degrees. In this article, I draw from a series of interviews conducted between 2011 and 2018 with 13 of these Iraqi refugees. My aim is to more fully understand and document their college-going experiences in the US. Framed by notions of deservingness and coloniality in education, this study is driven by two questions: In what ways and by whom are Iraqi refugees with Special Immigrant Visas positioned with regard to deservingness and worthiness in higher education? How do they position themselves? I explore how notions and discourses of deservingness, and their practical and political application, affect the resettlement experiences of these Iraqi refugees. The findings indicate that, because of their Special Immigrant Visa designation and their work with the Allied Forces, these refugees are positioned, and position themselves, not only as deserving but sometimes as being owed a college education. The study offers insights into the long-term effects crisis has on the education of those who are far removed, both geographically and temporally, from a crisis-affected area where they once lived.